A dual-emission carbon dots-based nonenzymatic fluorescent sensing platform for simultaneous detection of parathion-methyl and glyphosate. (1st March 2023) - Yang, Yangyu; Tong, Xia; Chen, Yuxia; Zhou, Rongrong; Cai, Guihan; Wang, Tongtao; Zhang, Shuihan; Shi, Shuyun; Guo, Ying
Graphical abstract: Highlights: Dual-emissive CDs have been synthesized by hydrothermal treatment of mulberry leaves and sodium hydroxide. CDs-based nonenzymatic fluorescent platform for pesticides sensing was developed. Dual-channel strategy was developed for simultaneously detecting parathion-methyl and glyphosate. Parathion-methyl and glyphosate were detected in real samples sensitively, selectively, and accurately. Combination of dual-emission CDs and OR logic gate can predict food, herbal, or environmental safety. Abstract: Simultaneous and high-performance detection of pesticides is still a considerable challenge and urgent need. Herein, a dual-emission carbon dots (CDs)-based nonenzymatic fluorescent sensing platform has been developed, which shows excellent sensitivity and selectivity in simultaneously detecting parathion-methyl (MP) and glyphosate. CDs with emissions at 440 nm (bCDs) and 660 nm (rCDs) were prepared by hydrothermal treatment of mulberry leaves and sodium hydroxide. bCDs response to hydrolyzed MP via inner filter effect, while rCDs sense glyphosate with the aid of Cu 2+ by static quenching effect. Excellent linear correlations were found for MP (0.3–65.0 μM) and glyphosate (1.0–110.0 μM) with limits of detection at 0.14 and 0.60 μM. Notably, the presented dual-channel strategy was successfully applied in simultaneously detecting MP and glyphosate in food/herbal samples with acceptable recoveries, good precision, and high selectivity. Moreover, an OR logic gate was achieved for estimating food, herbal, or environmental safety.